(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
The efficient waste management hierarchy is based on four priorities, reuse, recycle, energy recovery, deposit.Efficient energy recovery from non-recyclable textile materials (waste to energy) principles we study in this paper. Energy recovery from the fuel pellets consisting of waste textile materials and biomass depends on many factors. One of the main is to create a competitive form for the newly offered fuel (pellets from a mixture of biomass and textile), as well using a new generation of small-scale energy production facilities. Using already existing applications for efficient waste management is one of the circular economy aspects we lay on in this paper.Roughly estimated that the quantities of textiles separately collected will increased from 65 000 to 90 000 tons per year across the EU-27 from 2025. Reuse and recycling outlets will need to be created, as the current sorting and recycling capacities are not sufficient to process the anticipated volumes. However, it is also expected that at least half of these additional volumes will comprise non-reusable textile waste with specific flame retardant (FR) treatment. It is known that flame retardant is hazard by its adverse environmental impacts of FRs in their production and disposal phases.The objective of the paper is to review opportunities of elaboration a new type of the fuel pellets, and using them in industrial heat pellet boilers and combined heat and power CHP systems.Elaborated the new pellets from biomass (prepared by plasticization method) and chopped textile waste sized till 2-3 mm (by method separative milling) were tested in controlled combustion processes.Experiments were carried out by adding different proportions of textile waste to biomass pellets and the results obtained are summarized in the article